Strategy to empower Pancasila values through podcast media as digital citizens innovation - Nugroho, Dedy Ari; Anwar, Waris Yohn Candra (Universitas Negeri Yogyakarta, 2022)
Communication is one of the skills that need to be mastered by the 21st century generation. This includes communicating in harmony with the current pattern of the younger generation, which has a lot to do with the use of digital media. Podcasts are a form of innovation in communicating to spread Pancasila values in the lives of the younger generation. This research relates to the strategy taken to re-earth the values of Pancasila in the younger generation. This research was conducted at the Pancasila and Citizenship Education Study Program, Lambung Mangkurat University. This study focuses on 2 research points, including: (1) Podcast innovation in the educational environment, and (2) the strategy for implementing Citizenship Podcasts to promote Pancasila values. The results obtained in this research article refer to recommendations for innovative forms of communication that are more adaptive for the younger generation in grounding the values of Pancasila. This research article uses qualitative data analysis techniques by describing the data findings in the article presentation. The data collected is combined from observation data, interviews, and the experience of researchers in civic podcast activities. This research article is expected to be able to provide positive recommendations for the advancement of digital-based science.